Cloning and functional identification of a Chilo suppressalis‐inducible promoter of rice gene, OsHPL2. Issue 9 (10th May 2020) - Li, Hanpeng; Wang, Zhengjie; Han, Kehong; Guo, Mengjian; Zou, Yulan; Zhang, Wei; Ma, Weihua; Hua, Hongxia
Abstract: BACKGROUND: Promoters play a key role in driving insect‐resistant genes during breeding of transgenic plants. In current transgenic procedures for breeding rice resistance to striped stem borer ( Chilo suppressalis Walker, SSB), the constitutive promoter is used to drive the insect‐resistant gene. To reduce the burden of constitutive promoters on plant growth, isolation and identification of insect‐inducible promoters are particularly important. However, few promoters are induced specifically by insect feeding. RESULTS: We found rice hydroperoxide lyase gene ( OsHPL2 ) (LOC_Os02g12680) was upregulated after feeding by SSB. We subsequently cloned the promoter of OsHPL2 and analysed its expression pattern using the β ‐ glucuronidase (GUS) reporter gene. Histochemical assays and quantitative analyses of GUS activity confirmed that P HPL2 :GUS was activated by SSB, but did not respond to brown planthopper ( Nilaparvata lugens Stål, BPH) infestation, mechanical wounding or phytohormone treatments. A series of 5′ truncated assays were conducted and three positive regulatory regions (−1452 to −1213, −903 to −624, and −376 to −176) induced by SSB infestation were identified. P2R123‐min 35S and P2TR2‐min 35S promoters linked with cry1C of transgenic plants showed the highest levels of Cry1C protein expression and SSB larval mortality. CONCLUSION: We identified an SSB‐inducible promoter and three positive internal regions. Transgenic rice plants with the OsHPL2 promoter and its positive regions driving cry1C exhibited the expected larvicidal effect on SSB. Our study is the first report of an SSB‐inducible promoter that could be used as a potential resource for breeding insect‐resistant transgenic crops. © 2020 Society of Chemical Industry Abstract : A striped stem borer ( Chilo suppressalis Walker, SSB)‐inducible promoter and three positive internal regions, and transgenic rice plants with the OsHPL2 promoter and its positive regions driving cry1C, exhibited an expected larvicidal effect on SSB.